2023
DOI: 10.3390/cimb45040184
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E (APOE) Haplotypes in Healthy Subjects from Worldwide Macroareas: A Population Genetics Perspective for Cardiovascular Disease, Neurodegeneration, and Dementia

Abstract: Human APOE is a 299-amino acid long protein expressed and secreted in several tissues and body districts, where it exerts different functions mainly related to lipid metabolism, with specific activities around cholesterol transport and absorption/elimination. It has three main isoforms, determined by the pair of mutations rs7412-C/T and rs429358-C/T, which gives rise to the functionally different APOE variants ε2, ε3, and ε4. These have a distinct impact on lipid metabolism and are differentially implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Unlike other populations where rs781722239 and rs770562611 are rare, our study includes these SNPs, presenting a distinctive feature in our dataset. Looking into the characteristics associated with each of the non-common SNPs, we found that rs373985746 is involved in the AD modulation process [24]. Rs72654468 and rs781722239 were both found to be associated with CVD abnormalities [24,25].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Unlike other populations where rs781722239 and rs770562611 are rare, our study includes these SNPs, presenting a distinctive feature in our dataset. Looking into the characteristics associated with each of the non-common SNPs, we found that rs373985746 is involved in the AD modulation process [24]. Rs72654468 and rs781722239 were both found to be associated with CVD abnormalities [24,25].…”
Section: Discussionmentioning
confidence: 95%
“…Looking into the characteristics associated with each of the non-common SNPs, we found that rs373985746 is involved in the AD modulation process [24]. Rs72654468 and rs781722239 were both found to be associated with CVD abnormalities [24,25]. Rs769452 and rs267606664 were found to be involved in neurodegenerative and CVD abnormalities as well as free cholesterol and low-density lipoprotein measurements.…”
Section: Discussionmentioning
confidence: 95%
“…Among these genetic elements associated with cardiovascular diseases, the APOE gene has garnered substantial attention due to its associations with various health conditions [ 24 ]. In a case-control study investigating the signaling pathways related to structural changes in varicose veins, it was found that the expression of APOE genes was down-regulated in varicose veins compared to the control group [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 ApoE has several haplotypes with varying frequencies across populations, which may manifest differently depending on the context and the extent of influence of environmental factors. Additionally, the impact of these haplotypes may fluctuate depending on individual-related factors, such as sex, ethnicity, and age, 57 and individual differences in environmental characteristics might be partly explained by hereditary factors. 58,59 Therefore, interpreting G × E interactions might introduce bias if the environmental moderator is influenced by genetics itself, especially when the relevant genes can also directly impact the trait under scrutiny.…”
Section: Discussionmentioning
confidence: 99%